Meaning Used By Pranatacara in Javanese Wedding Ceremony “Panggih Manten” - Muhammad Natsir; Tiara Artha Dewi; Bahagia Saragih (Lakhomi Journal Scientific Journal of Culture, 2022)
This study used the descriptive qualitative method. The qualitative method was a research procedure which results in descriptive data, including written and oral word from the research objectives. The data used in this study were taken from the speech utterances by Pranatacara in "Panggih Manten" wedding ceremony in the Aeksongsongan. The researcher took the data from two Pranatacara and two Panggih Manten which taken from the speech utterances. The researcher used a source of theories about the semantic field by Knowles and Moon to support the thesis. Some steps were undertaken during the data collection: the process of selecting, focusing on the important things, simplifying, abstracting and transforming the data that appear in transcription. The results showed that the data into 23 metaphorical meanings from total two pranatacara of Javanese Wedding Ceremony or Panggih Manten. The dominant of metaphorical meaning was creative metaphor which had the highest percentage. The other result showed the least of metaphorical meaning was conventional meaning which had the lowest percentage. We took to identify and consider three things : metaphor, meaning, and connection by analysing and discussing metaphors in any depth. The percentage of the sequences Panggih Manten consisted of the opening, balangan gantal, injak telur, sinduran, dulangan, kacar kucur, sungkeman and the closing.